Replicação de cabeçalhos codificados em redes LR-FHSS - Knop, Diogo Nogueira (2024)
Long-Range Frequency-Hopping Spread Spectrum (LR-FHSS) has recently been introduced within the Long Range Wide Area Network (LoRaWAN) framework, aiming to mitigate packet collisions and enhance network capacity. This is achieved by replicating headers and segmenting data packets into smaller fragments randomly distributed across multiple channels to improve resilience against interference. Recent research within the LR-FHSS domain has highlighted the significance of header error rates in influencing the overall system error, indicating the limitations of traditional repetition codes for error correction. In response, this thesis proposes a network-coded-aided inter-header combination scheme to enhance header protection against both erasures and collisions. Through analytical and simulation-based investigations, the study demonstrates a substantial reduction in packet error rates by more than one order of magnitude across various scenarios, underscoring the effectiveness of the proposed scheme in enhancing reliability and resilience in LoRaWAN deployments.